Atividade acaricida de siloxano organo-modificado e associações acaricidas em Rhipicephalus microplus - Ries, Ananda Segabinazzi (2021)
Rhipicephalus microplus, is known worldwide for causing great losses in cattle farming. Through its blood-sucking habit, it causes damage to its host, ranging from productive losses to the transmission of diseases. The main alternative to controlling this mite is the use of chemicals. However, the indiscriminate use of these compounds has categorically contributed to the acceleration of the development processes of tick resistance to acaricides, contributing to the current scenario where most of the tick population is resistant to one or more active ingredients available on the market, as well as their associations. Taking these points into account, the present work aims to determine the acaricidal activity of organo-modified siloxane in a single formulation or associated with different commercial products and piperonyl butoxide (BPO) against R. microplus. In vitro tests of immersion of teleogens were performed, using 10 treatment groups: control group (T1), 0.5% siloxane (T2), 1% siloxane (T3), 2% siloxane (T4), 0.5% siloxane + 5% BPO (T5), 1% siloxane + 5% BPO (T6), 2% siloxane + 5% BPO (T7), commercial product (T8), 0.5% siloxane + commercial product (T9) and siloxane 1 % + commercial product (T10). After immersion, the teleogens were incubated in an oven with controlled temperature and humidity (28ᴼC, > 80% humidity) for 14 days to evaluate oviposition. Under the same humidity and temperature conditions, the apparently viable eggs were stored in test and sealed with hydrophobic cotton for 26 days to assess hatchability. Together, a telogen immersion test was performed using siloxane 5% and siloxane 2.5% + BPO 10% to assess the histopathological changes resulting from the action of these compounds. For this, 3 groups were formed: control (G1), treated with 5% siloxane (G2) and treated with 2.5% siloxane + 10% BPO (G3). After immersion, the telogens were incubated for 0, 2, 4, 8, 12, 24, 36, 48, 60, 72, 84, 96, 120, 144 and 168 hours. At the end of each established period, five teleogens corresponding to each of these periods were immersed in 10% formaldehyde for fixation and subsequent preparation of slides for histopathological analysis. The unassociated organomodified siloxane showed an acaricidal efficacy of 93.88% at its concentration of 2%. When associated with BPO 5%, it reached 100% efficiency in any of the tested concentrations (0.5, 1 and 2%) and associated with commercial products, siloxane enhanced their effectiveness. In histopathological evaluations, cellular changes were observed in both treatments. In the group treated with siloxane (G2), total cell disintegration was observed after 120 hours and in the group treated with siloxane + BPO (G3), total disintegration was observed after 96 hours. Thus, organo-modified siloxane is characterized as an option to combat R. microplus, either in its pure or associated form, and can also be used as an enhancer for commercial products.